Spiritually integrated care for PTSD: A randomized controlled trial of "Building Spiritual Strength". (September 2018) - Harris, J. Irene; Usset, Timothy; Voecks, Cory; Thuras, Paul; Currier, Joseph; Erbes, Christopher
Highlights: A randomized controlled trial was conducted for a spiritually integrated group therapy. Veterans in both the experimental and control groups showed similar levels of reduction in PTSD symptoms. Veterans in the spiritually integrated condition had greater reductions in spiritual distress. Abstract: Previous literature documents important cross-sectional and longitudinal relationships between spiritual distress and posttraumatic stress disorder (PTSD) outcomes. This study tests the efficacy of a spiritually integrated intervention "Building Spiritual Strength" (BSS) that can be delivered by trained chaplains. The intervention addresses spiritual concerns expressed by trauma survivors, including concerns in relationship with a Higher Power, difficulty with forgiveness, and theodicy. In a randomized controlled trial with blinded assessment, veterans were randomized to engage in a BSS condition ( n =  71) or Present Centered Group Therapy (PCGT; control) condition ( n =  67) with assessments at baseline, posttreatment, and a two-month follow up. Both groups showed similar, statistically significant reductions in symptoms of PTSD as measured by the Clinician Administered PTSD Scale (CAPS). BSS was shown to be more effective than PCGT in treating distress in relationship with a Higher Power. This was the second clinical trial of BSS with promising results and highlights the need for further study in psychospiritual interventions. More research is warranted on BSS being offered by non-specialized chaplains and on the application of BSS in suicide prevention.